PERAN PEMBELAJARAN GEOGRAFI TERHADAP KEPEDULIAN LINGKUNGAN DAN PERILAKU KERUANGAN DI SMA KABUPATEN PANDEGLANG - Rasi Yeni Mustika, - (2021)
The attitude of caring for the environment and spatial behavior is very important for students related to the affective domain of learning outcomes and can be induced through learning, one of the learning materials that encourages environmental awareness attitudes in schools is the subject of geography, geography learning, what is learned, how to seek help and assistance the formation of attitudes and behavior of students who care about the environment. Qualitative research methods, The purpose of this study is to analyze the role of geography learning on environmental awareness in Pandeglang District Public High School. Data is collected through surveys and in-depth interviews, and data is processed using the SPSS application. The results of the descriptive analysis table results obtained obtained significant results from the variable learning geography will increase financial motivation in SMA Kab. Pandeglang has the lowest value of 65 and the highest value of 94, so that in this case can be enlarged, spatial habits will increasingly increase